2008
DOI: 10.1254/jphs.fp0070736
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mast Cell Mediators on Migration of SW756 Cervical Carcinoma Cells

Abstract: Abstract. The role of mast cell mediators on cervical cancer cell migration was assessed using an in vitro assay of scratch wound healing onto monolayers of HPV18-positive cervical carcinoma cells (SW756). Migration of SW756 cells was accelerated by co-culture with the mast cell line LAD2. This effect was inhibited by the H1R antagonist pyrilamine and the cannabinoid agonists 2-arachidonylglycerol (2AG) and Win 55,212-2. Therefore, the specific effects of histamine and cannabinoids on SW756 migration and LAD2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…Accordingly, the antiallergic compound tranilast inhibits cell migration and invasion in human malignant glioma cells blocking H1 receptors (Platten et al, 2001). A divergent response (stimulatory or inhibitory) on the migration rate of SW756 cervical carcinoma cells has been disclosed by histamine acting on H1 receptor or H4 receptor, respectively (Rudolph et al, 2008). However, as far as we know, our work is the first report about histamine-modulated migration and invasion through H4 and H2 receptors in breast tumor cells.…”
Section: Histamine and Histamine Agonists Modulate Mda-mb 231 Cells Mmentioning
confidence: 67%
“…Accordingly, the antiallergic compound tranilast inhibits cell migration and invasion in human malignant glioma cells blocking H1 receptors (Platten et al, 2001). A divergent response (stimulatory or inhibitory) on the migration rate of SW756 cervical carcinoma cells has been disclosed by histamine acting on H1 receptor or H4 receptor, respectively (Rudolph et al, 2008). However, as far as we know, our work is the first report about histamine-modulated migration and invasion through H4 and H2 receptors in breast tumor cells.…”
Section: Histamine and Histamine Agonists Modulate Mda-mb 231 Cells Mmentioning
confidence: 67%
“…Histamine acting via H 1 R in cervical cancer cells could be pro-migratory, but when acting via H 4 R could inhibit migration. On the other hand, other results also showed that cervical carcinoma cell mediators can activate mast cells to degranulate, demonstrating an active and dynamic cross-talk between tumour cells and infiltrating mast cells as shown in morphologic studies of neoplastic tissues (Rudolph et al, 2008). In the light of these results, further investigations have to be done in order to elucidate the physiological role of histamine receptors on cell proliferation, as well as its implication in gynaecologic cancer progression with a potential interest for cancer treatment.…”
Section: Histamine Receptors In Gynaecologic Cancersmentioning
confidence: 81%
“…Accordingly, mast cells were recently demonstrated as a source of promigrative chemoattractants acting as possible targets of cannabinoids (Rudolph et al, 2008). In the latter study, cancer cell migration initiated by mast cells was down-regulated by the endocannabinoid 2-arachidonylglycerol (2-AG) as well as by the synthetic cannabinoid WIN-55,212-2 in the scratch wound healing assay.…”
Section: N-(2-hydroxyethyl)-7z10z13z16z-docosatetraenamidementioning
confidence: 99%